An efficient morphology generation and level set representation of cementitious microstructures with arbitrarily shaped aggregates and cracks via extended finite elements. (15th August 2018) - Huang, Junjie
Highlights: An efficient level set representation of cementitious microstructures is proposed. An improved approach to simulate aggregate geometric shape and surface texture is presented. Support mapping representation of arbitrarily shaped aggregates is explored. A new packing algorithm for dense packing of aggregate particles in concrete RVEs is developed. The proposed technique is coupled to the XFEM for modeling micro-scale crack propagation. Abstract: Concrete has a random and complex microstructure, the mesh generation of which could be challenging and time-consuming. This research presents a numerical procedure for morphology generation and level set representation of realistic cementitious microstructures without meshing the internal material interfaces. Central to the proposed numerical method is the exploitation of a vector level set function in the description of arbitrarily shaped aggregate inclusions, which allows bypassing the orthogonal projection operation on the inclusion interface as well as the determination of the outward normal. The proposed level set method is then coupled to the extended finite element method to simulate crack propagation in cement-based materials. To realistically simulate the microstructure of concrete, an improved approach that is capable of reproducing the complex geometric shape and surface texture of aggregates is proposed. To enhance the computational efficiency, a packing algorithm that mimics the settling of soil particles and enables dense aggregate packing patterns is developed to speed up the process of placing the generated aggregates into representative volume elements. After that, a series of numerical experiments are conducted to evaluate the accuracy and efficiency of the new technique. The evaluation demonstrates the effectiveness and potential of the proposed method.